Republic of Belarus : Request for Stand-By Arrangement; Staff Report; Staff Supplement and Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Belarus. (IMF Staff Country Reports; Country Report ;, 2009)
Belarus' economic growth has been impressive in the last few years. Belarus' economic program is designed to facilitate adjustment to external shocks and reduce vulnerabilities. It includes a number of structural reforms on issues that are critical to the mitigation of vulnerabilities. On structural policies, the program places economic liberalization as a priority, particularly price liberalization. The program also envisages efforts to enhance the role of the private sector by reducing the distortion of taxes and the regulatory burden on private companies, and continuing privatization efforts.